2018
DOI: 10.1039/c8fd00079d
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry-dependent hydrogen bonds stabilise stacked conformations in jet-cooled cyclic dipeptides: (LD) vs. (LL) cyclo tyrosine–tyrosine

Abstract: Tyrosine-containing cyclic dipeptides based on a diketopiperazine (DKP) ring are studied under jet-cooled conditions using resonance-enhanced multi-photon ionisation (REMPI), conformer-selective IR-UV double resonance vibrational spectroscopy and quantum chemical calculations. The conformational landscape of the dipeptide containing natural L tyrosine (Tyr), namely c-LTyr-LTyr strongly differs from that of its diastereomer c-LTyr-DTyr. A similar family of conformers exists in both systems, with one aromatic ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(78 citation statements)
references
References 73 publications
7
70
1
Order By: Relevance
“…These values are close to those for tyrosine, which range from 35491 cm -1 to 35650 cm -1 depending on the conformer [41][42][43][44][45] or to those for cyclo Tyr-Tyr. 12 Several vibronic bands appear in these spectra, suggesting strong vibronic activity and/or coexistence of conformers. The spectrum of c-LL shows four origin-like transitions noted A (35498 cm -1 ), B (35532 cm -1 ), C (35592 cm -1 ), D (35673 cm -1 ) in Figure 4.…”
Section: Iii-2 a Electronic Spectroscopymentioning
confidence: 95%
See 2 more Smart Citations
“…These values are close to those for tyrosine, which range from 35491 cm -1 to 35650 cm -1 depending on the conformer [41][42][43][44][45] or to those for cyclo Tyr-Tyr. 12 Several vibronic bands appear in these spectra, suggesting strong vibronic activity and/or coexistence of conformers. The spectrum of c-LL shows four origin-like transitions noted A (35498 cm -1 ), B (35532 cm -1 ), C (35592 cm -1 ), D (35673 cm -1 ) in Figure 4.…”
Section: Iii-2 a Electronic Spectroscopymentioning
confidence: 95%
“…This contrasts to the previous findings on neutral or protonated cyclo PhePhe, or neutral cyclo Ty-Tyr, in which homochirality was always favored. [11][12]14 Among the studied DKP dipeptides, cyclo Tyr-Pro stands out by the cyclic nature of the proline residues, which introduces additional conformational bias. As a result, the NH… interaction,…”
Section: C-llmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent combined theoretical (DFT calculations) and experimental (resonance-enhanced multiphoton ionisation and double resonance infrared ultraviolet) spectroscopic studies have examined jet-cooled cyclic dipeptides in gas phase. BenNasr et al [30] found that the conformational landscape of cyclo(L-Tyr-L-Tyr) strongly differs from that of its diastereomer cyclo(L-Tyr-D-Tyr). The same techniques were employed to study the conformational landscape of cyclo(L-Tyr-L-Pro) and cyclo(L-Tyr-D-Pro) [31], where the simulation of the vibronic pattern of the S 0 -S 1 transition was necessary to assign the observed spectra to either folded or extended conformations.…”
Section: Introductionmentioning
confidence: 99%
“…[20] We have undertaken the study of DKP dipeptides in different environments, either in the solid state by vibrational circular dichroism (VCD), protonated in a room-temperature ion trap, or under supersonic expansion conditions). [21][22][23][24][25] The aim of this study is to understand the factors that determine the structural differences between the molecule with residues of natural chirality L and that containing one D residue. This work is part of our recent studies on chirality effects in cyclic systems at low temperature.…”
Section: Introductionmentioning
confidence: 99%